SYSTEMATICS LITERATURE REVIEW: Eksplorasi Etnomatematika Perhitungan Hari Baik pada Aktivitas Masyarakat - Muchamad Ari Choirudin; Arfatin Nurrahmah (CV. ALIM'SPUBLISHING, 2025)
Mathematics is one of the important subjects to be applied in daily life. This mathematical concept can be combined with culture, one of which is ethnomathematics. This ethnomathematics always relates the concept of mathematics to the culture applied in daily life. One of them is the calculation of good days, this calculation applies mathematical concepts including: addition, subtraction, division, number patterns, modulos and others. This article aims to take a deeper look at the application of ethnomathematical concepts by looking at the results of previous journal reviews. The method used in this study is the Systematic Literature Review (SLR) method. The Systematic Literature Review method is used to identify, evaluate, and interpret all research in various fields with interesting topics with specific research questions. Data collection was carried out by reviewing articles on ethnomathematics of good day calculations published in the 2020-2024 period. The result of this study is the existence of ethnomathematics of good day calculation where the concept of mathematics is contained in every work and activity of society.